Efektivitas Teknik Imajinasi terhadap Motivasi Berprestasi Peserta Didik SMPN 1 Makassar. - Ulfah (Institut Agama Islam Negeri Parepare, 2022)
This research aims to determine the effectiveness of imagination techniques in increasing achievement motivation. This research uses a quantitative experimental approach. The research used was a true-experimenta design, with a pretest-posttest control group design. The research results showed that the achievement motivation of students in both groups was in the medium category in the pre-test. while in the post-test the experimental group and control group were in the high category. The achievement motivation score in the experimental group experienced a higher increase and the control group also experienced an increase, but the increase was quite low. The results of the Gain score analysis obtained a mean increase for the experimental group of 10.37 and for the control group of 1.17. The results of the post-test showed quite significant differences, the mean of the experimental group was higher than the mean of the control group. This shows that there is a significant difference in student achievement motivation between students who were treated and those who were not treated with group guidance in the form of imagination techniques in participants at SMP Negeri 1 Makassar. It was concluded that imagination techniques had a real effect on students' achievement motivation.